Identifying and Supporting Approaches in Pakistani Schools to Address Learning Disabilities - Muhammad Adil; Abdul Rehman; Natalia Shabbir; Kalsoom Mahsud; Shafaq Safdar (Research Journal of Psychology, 2025)
Learning disabilities (LD) have profound negative impact on students’ academic achievement and development but again LD is either unrecognized or under addressed in school in Pakistan. In this quantitative research, the methods and practices that help learners with LD in the Pakistani schools are determined with the main purpose of solving the problem. The total sample comprised two hundred participants, teachers, and school administrators who were administered structured questionnaires for assessing LD awareness, intervention, and institutional support measures for students with LD. Therefore, the quantitative analysis of congruency and in congruency of knowledge with educators and access to specialized resources indicate a moderate level of awareness. The results point to a require for specific teacher professional development, changes at a policy level, coupled with the inclusion and implementation of scientifically based instruction to effectively address learning of students with LD. The current study offers practical implications to the policy makers and educators in order to deal with the barriers of learning disabilities in Pakistani context.